Annual report 1987 (Guyana Marketing Corporation GeorgetownGY, 1988)
Describes the 1987 performance of the Guyana Marketing Corporation focusing on market activities; distribution and training of manpower resources; technical assistance; funding; constraints and successes. Uses tables to portray the volume, type, shipping method, and importing country of non-traditional agricultural exports. Outlines the corporation's 1988 work programme.
Filed with CARTIS documents